The Internal Gross Product (GDP) and its relationship with tax income in Peru 2007-2018 - Rojas Fernández, José (2019)
Objective: To analyze the relationship between the Gross Domestic Product and the Tax Revenue collected by the Peruvian State. Method: The research approach is quantitative descriptive and correlational type, whose design was non-experimental and longitudinal, that is, documentary information was collected on tax collection and the internal product from 2007 to 2018 of the National Superintendence Customs and Tax Administration (SUNAT). Results: There is no variability in the gross domestic product as well as in the tax collection; The data is homogeneous in each variable. Conclusions: It is concluded that there is a significant relationship between the gross domestic product and the Tax Revenue, this result was confirmed with the Pearson correlation coefficient, which was 0.9401, defined as a high correlation between the two indicated variables.